(untitled) (Annual of the Faculty of Philosophy in Skopje, 2016)
The views on the issue of sexuality ofpeople with intellectual disability are very slowly and slightly changing. Sexuality of these people is taboo in both, day centers where they place their treatment, and their families. The survey was designed to determine whether employees in day care centers in Kumanovo, Veles, Bitola and Kriva Palanka are prepared for implementation of activities from the area of sexual education. The survey covered 64 parents of children with moderate and severe intellectual disabilities and 19 persons employed in centers that are directly involved in their treatment. Both groups of respondents believe that the actions in the field of sexual education should be applied, but as a precondition employees in day care centers and parents should receive training on their application. Additional problem is the lack of teaching aids for the implementation of these activities.